2012
DOI: 10.1186/1472-6963-12-409
|View full text |Cite
|
Sign up to set email alerts
|

Transversal analysis of public policies on user fees exemptions in six West African countries

Abstract: BackgroundWhile more and more West African countries are implementing public user fees exemption policies, there is still little knowledge available on this topic. The long time required for scientific production, combined with the needs of decision-makers, led to the creation in 2010 of a project to support implementers in aggregating knowledge on their experiences. This article presents a transversal analysis of user fees exemption policies implemented in Benin, Burkina Faso, Mali, Niger, Togo and Senegal.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 19 publications
0
27
0
4
Order By: Relevance
“… 21 There is some evidence that the policy in Burkina Faso reduced out-of-pocket expenses and did not have an adverse effect on quality. 22 23 A further interesting point why uptake may have been greater in Burkina Faso was because the fee set for normal deliveries was significantly higher than the real cost. As highlighted in our interviews, the guidelines on how this money should be allocated were not clear, and in particular what proportion could be claimed by staff as bonuses.…”
Section: Resultsmentioning
confidence: 99%
“… 21 There is some evidence that the policy in Burkina Faso reduced out-of-pocket expenses and did not have an adverse effect on quality. 22 23 A further interesting point why uptake may have been greater in Burkina Faso was because the fee set for normal deliveries was significantly higher than the real cost. As highlighted in our interviews, the guidelines on how this money should be allocated were not clear, and in particular what proportion could be claimed by staff as bonuses.…”
Section: Resultsmentioning
confidence: 99%
“…In Africa, "80 percent of countries (37 of the 41 countries that had use fees) have implemented reforms to reduce or eliminate user fees" (Cotlear and Rosemberg, 2018). However, several studies have shown that the decisions to introduce these user fees exemption policies in Africa were often electorally motivated, sudden, prompted by external pressures, and consequently very chaotic in their implementation (Meessen et al, 2011;Ridde, Queuille, et al, 2012;Olivier de Sardan and Ridde, 2015;Gautier and Ridde, 2017), even if their effects were often beneficial for populations. This was still the case at the end of 2017, such as in Gabon, where the President suddenly announced exemption from payment for deliveries without anything having been prepared on the ground.…”
Section: Introductionmentioning
confidence: 99%
“…These initiatives consisted of subsidizing medical interventions by 60%–80%. Consequently, women would pay 11 000 XOF (CFA Francs; US $18.3) for a cesarean delivery; while transfer of patients from a primary health center to a hospital became free [7–9].…”
Section: Introductionmentioning
confidence: 99%
“…Before and after implementation of this national initiative, other local initiatives (at district level) were developed to reduce the financial barriers for pregnant women and children under 5 years. Some of these initiatives have been documented in the literature [7–12].…”
Section: Introductionmentioning
confidence: 99%